فاعلية توظيف التجارب الافتراضية في تنمية عمليات العلم التكاملية في الكيمياء لدى طالبات الصف العاشر في اربيل - احمد حمه الهام; سليمان حسو اشقي (Journal of College of Education, 2020)
The aim of the current research is to know "the effectiveness of using virtual lab in the improvement of integrative science processes for chemistry subject among students of the tenth grade in Erbil". In order to achieve the goals and test the hypotheses of the research, 60 female students were selected from ‘Nahrayn High School for Girls’ for the academic year 2019-2020 as the research participants. The participants were randomly divided into two groups, one of which was an experimental one who were taught using the virtual laboratory, and the second group students were taught according to the current, ordinary method after conducting integrated science processes pre-test to both groups of students. For achieving the research objectives and testing its hypotheses, certain tools were to be provided, such as preparing the virtual laboratory software and designing the integrated science processes test. The test consisted of 15 items, and after verifying its validity and consistency, the experiment was applied for seven academic weeks, then the post-application of the research tool was conducted. The results showed that there was a statistically significant difference at the level of significance (0.05) between the average score of the students of the experimental group and the average score of the ordinary group in the post-application in the integrated science processes test as a whole. And there existed the presence of statistically significant differences at the level (0.05) between the average score of the students of the experimental group and the average score of the control group in the test of the integrated science processes before and after in each of the fields (T. Procedural corporal, controlling variables and assuming hypotheses). At last,the research concluded a set of related recommendations.